Biomechanics of two external fixator devices used in rat femoral fractures. Issue 2 (8th February 2019) - Osagie‐Clouard, Liza; Kaufmann, Joshua; Blunn, Gordon; Coathup, Melanie; Pendegrass, Catherine; Meeson, Richard; Briggs, Timothy; Moazen, Mehran
ABSTRACT: The use of external fixators allows for the direct investigation of newly formed interfragmentary bone, and the radiographic evaluation of the fracture. We validated the results of a finite element (FE) model with the in vitro stiffness' of two widely used external fixator devices used for in vivo analysis of fracture healing in rat femoral fractures with differing construction (Ti alloy ExFix1 and PEEK ExFix2). Rat femoral fracture fixation was modeled using two external fixators. For both constructs an osteotomy of 2.75 mm was used, and offset maintained at 5 mm. Tufnol, served as standardized substitutes for rat femora. Constructs were loaded under axial compression and torsion. Overall axial and torsional stiffness were compared between the in vitro models and FE results. FE models were also used to compare the fracture movement and overall pattern of von Mises stress across the external fixators. In vitro axial stiffness of ExFix1 was 29.26 N/mm ± 3.83 compared to ExFix2 6.31 N/mm ± 0.67 ( p * < 0.05). Torsional stiffness of ExFix1 was 47.5 Nmm/° ± 2.71 compared to ExFix2 at 19.1 Nmm/° ±1.18 ( p * < 0.05). FE results predicted similar comparative ratios between the ExFix1 and 2 as the in vitro studies. FE results predicted considerably larger interfragmentary motion in the ExFix2 comparing to ExFix1. We demonstrated significant differences in the stiffness' of the two external fixators as one would expect from such variable designs; yet, importantly we validated the utility of an FE model for the analysis and prediction of changes in fracture mechanics dependent on fixator choice. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:293–298, 2019.